Ka band enabling technologies for high throughput satellite (HTS) communications. (26th November 2015) - Hasan, Mohamed; Bianchi, Christopher
Abstract: Global demands for personal, businesses and governments connected data continue to challenge our communication technologies and infrastructure. Both wired and wireless terrestrial communications systems are realizing advancements in technologies and their applied infrastructure enhancements. These ever evolving terrestrial communication systems are providing for increased data capacity, an enhanced quality of service and a lower cost per bit for all users. Satellite systems are especially challenged in order to remain relevant for these same enhancements in order to augment and compete with these terrestrial global communication systems. In order to meet these global demands the next generation satellite communications systems are evolving by advancing their own technologies and infrastructure. The resulting next generation communication satellite systems include utilization of the Ka frequency band and also through the application of other key advancements in antenna systems and processing payloads. This paper provides an overview of many of the communication satellite system advancements which are in part enabled through the utilization of the Ka frequency band. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Satellite communications are ever evolving by leveraging newer Ka frequency bands, sophisticated payload processing technologies and higher capacity architectures to keep up with an insatiable global thirst for real‐time connectivity in our un‐plugged world. These developments have resulted in a newer class of overhead wireless communication known as high throughput satellites (HTS). While a foundational corner stone for enhanced HTS is the migration to Ka‐band, application of advanced technologies is enabling the creation of a newer class of HTS. With the potential of exceeding total throughput of 100's of Gbps, this paper explores some of the adaptive, agile and infrastructure technologies that will make the next generation of HTS possible.